2020
DOI: 10.1108/ijlma-10-2018-0245
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity, corporate governance and financial risk disclosure in the UK

Abstract: Purpose This study aims to investigate the impact of corporate governance (CG) mechanisms on financial risk reporting in the UK. Design/methodology/approach The study uses a panel data of 50 non-financial firms belonging to 10 industrial sectors listed on the London Stock Exchange in the period 2011-2015. Multivariate regression techniques are used to examine the relationships. Findings The findings of this study reveal that CG has a significant influence on financial risk disclosure. Specifically, it is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 58 publications
(150 reference statements)
6
63
1
Order By: Relevance
“…Researchers, policymakers, and practitioners suggest that well‐structured boardrooms enhance the performance and organizational policymaking for all companies (Aggarwal, Jindal, & Seth, 2019; Alnabsha, Abdou, Ntim, & Elamer, 2018; Alshbili, Elamer, & Beddewela, 2019; Baker, Pandey, Kumar, & Haldar, 2020; Birindelli, Iannuzzi, & Savioli, 2019; Ciocirlan & Pettersson, 2012; Sitthipongpanich & Polsiri, 2014). Similarly, it has been documented in the literature that more diversified board may bring benefits to the boardroom by improving connections and networking that could be beneficial for expanding business in areas might be overlooked (Bufarwa, Elamer, Ntim, & AlHares, 2020; Gulamhussen & Santa, 2015; Haque & Ntim, 2020; Khan, Hussain, et al, 2019; Khan, Khan, & Saeed, 2019; Pucheta‐Martínez & Bel‐Oms, 2019; Shahab et al, 2020; Shahab, Ntim, Chengang, Ullah, & Fosu, 2018; Shahab, Ntim, Ullah, Yugang, & Ye, 2020). Board diversity, for example, can assist firms in gaining different information and wider exposure to the environment from suppliers, customers, policymakers, as well as social groups and competitors (Elsharkawy, Paterson, & Sherif, 2018; Horbach & Jacob, 2018; Tingbani, Chithambo, Tauringana, & Papanikolaou, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Researchers, policymakers, and practitioners suggest that well‐structured boardrooms enhance the performance and organizational policymaking for all companies (Aggarwal, Jindal, & Seth, 2019; Alnabsha, Abdou, Ntim, & Elamer, 2018; Alshbili, Elamer, & Beddewela, 2019; Baker, Pandey, Kumar, & Haldar, 2020; Birindelli, Iannuzzi, & Savioli, 2019; Ciocirlan & Pettersson, 2012; Sitthipongpanich & Polsiri, 2014). Similarly, it has been documented in the literature that more diversified board may bring benefits to the boardroom by improving connections and networking that could be beneficial for expanding business in areas might be overlooked (Bufarwa, Elamer, Ntim, & AlHares, 2020; Gulamhussen & Santa, 2015; Haque & Ntim, 2020; Khan, Hussain, et al, 2019; Khan, Khan, & Saeed, 2019; Pucheta‐Martínez & Bel‐Oms, 2019; Shahab et al, 2020; Shahab, Ntim, Chengang, Ullah, & Fosu, 2018; Shahab, Ntim, Ullah, Yugang, & Ye, 2020). Board diversity, for example, can assist firms in gaining different information and wider exposure to the environment from suppliers, customers, policymakers, as well as social groups and competitors (Elsharkawy, Paterson, & Sherif, 2018; Horbach & Jacob, 2018; Tingbani, Chithambo, Tauringana, & Papanikolaou, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Consequently, the focus of the study is to empirically examine the impact of corporate governance on risk disclosures in deposit money banks in Nigeria. Unlike other studies (Ntim et al, 2013;Elzahar and Hussainey, 2012;Dionne and Triki, 2012;Manab et al, 2010;Bufarwa et al, 2020;Lotfi and Mohammadi, 2014;Connelly et al, 2010;Elshandidy et al, 2013 andHasan et al, 2020) that make use of single estimation approach majorly panel regression and without paying attention to consistency of estimates which is one of the causes of mixed and inconclusive findings in the literature; this study examines the effect of corporate governance on risk disclosure using a combination of both bootstrapped ordinary least square (OLS-B) regression, panel regression, and quantile regression to examine the consistency of the results across methods. Since the evolvement of bootstrap procedure proposed by Efron (1979) for statistical analysis of independent and identically distributed (i.i.d.…”
mentioning
confidence: 73%
“…Ntim et al (2013) observe that "corporate boards that are made up of diverse gender backgrounds tend to increase the probability of there being more voluntary disclosures. Using listed firms in the UK, (Bufarwa et al, 2020), examined linkages between governance and risk disclosures and the finding revealed that BGD has a positive effect on the level of risk disclosure.…”
Section: Bgd and Risk Disclosuresmentioning
confidence: 99%
“…The corporate governance mechanisms quality is the central influencing factor of corporate financial policies, including cash holding (Abdelfattah et al 2020 ; Abdou et al 2020 ; AlHares et al 2020 2020a ; Alnabsha et al 2018 ; Alshbili et al 2019 ; Alshbili and Elamer 2020 ; Hazaea, Zhu, et al , b ; Khatib et al 2020 ). Corporate governance practices are expected to ensure that executives act in the best interest of stockholders (Asante-Darko et al 2018 ; Bufarwa et al 2020 ; El-Dyasty and Elamer 2020 ; Elamer et al 2018 , 2020 , 2019 ; Elamer and Benyazid 2018 ; Elmagrhi et al 2018 ; Hazaea et al 2020a ). Jensen ( 1986 ) stressed that executives are reluctant to disburse the extra cash among stockholders to secure their benefits by investing it in unprofitable projects, which might destroy corporates' valuation.…”
Section: Bibliometric Analysismentioning
confidence: 99%